2022
DOI: 10.3390/antiox11020429
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Properties of a Cocoa Shell Extract: Mechanism of Action and Effect on Endothelial Dysfunction in Aged Rats

Abstract: Cocoa has cardiovascular beneficial effects related to its content of antioxidant phytochemicals. Cocoa manufacturing produces large amounts of waste, but some by-products may be used as ingredients with health-promoting potential. We aimed to investigate the vasoactive actions of an extract from cocoa shell (CSE), a by-product containing theobromine (TH), caffeine (CAF) and protocatechuic acid (PCA) as major phytochemicals. In carotid and iliac arteries from 5-month and 15-month-old rats, we investigated CSE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
(55 reference statements)
2
16
0
Order By: Relevance
“…From each litter, some rats were studied at the age of 21 days (weaning) and others at the age of 6 months (adult), using 1-2 rats from each sex and age and the rest of the animals were aged for other studies. We have previously described that MUN male rats develop hypertension by the age of 6 months, assessed either by direct intra-arterial measurement under anesthesia or by tail-cuff plethysmography [33][34][35][36][37][38][39][40][41]. In the present study, tail-cuff plethysmography measurements from adult rats also showed that MUN males had significantly higher systolic blood pressure (SBP) compared to controls (control= 136.9±3.1 mm Hg, n=7; MUN=163.1±3.6, n=8; p=0.004).…”
Section: Maternal Undernutrition Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…From each litter, some rats were studied at the age of 21 days (weaning) and others at the age of 6 months (adult), using 1-2 rats from each sex and age and the rest of the animals were aged for other studies. We have previously described that MUN male rats develop hypertension by the age of 6 months, assessed either by direct intra-arterial measurement under anesthesia or by tail-cuff plethysmography [33][34][35][36][37][38][39][40][41]. In the present study, tail-cuff plethysmography measurements from adult rats also showed that MUN males had significantly higher systolic blood pressure (SBP) compared to controls (control= 136.9±3.1 mm Hg, n=7; MUN=163.1±3.6, n=8; p=0.004).…”
Section: Maternal Undernutrition Modelmentioning
confidence: 99%
“…Endothelial function was assessed in iliac arteries by isometric tension recording as previously described [35]. Briefly, 3-mm-long arterial segments were mounted on 168-μm-diameter iron wires and placed on organ bath chambers containing KHS, at 37 °C with carbogen gas (95% O 2 and 5% CO 2 ).…”
Section: Assessment Of Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the results of this study, we have previously shown a significant increase in the NOX activity in arteries obtained from a high-cholesterol-fed rats group, which was significantly reduced in vessels from rats fed the high-cholesterol enriched with onion diet. Also, recently Rodríguez-Rodríguez et al (2022) [ 123 ] indicated the capacity of cocoa shell extract to reduce superoxide anion levels in aged rats. Additionally, Rozentsvit et al (2017) [ 124 ] found the ellagic acid significantly decreased endothelial ROS levels and ameliorated the impairment of vascular relaxation induced by high glucose in Sprague–Dawley rats, suggesting that polyphenols exert a vasculo-protective effect under diabetic conditions via an antioxidant effect that involves inhibition of ERK1/2 and downregulation of NOX4.…”
Section: Resultsmentioning
confidence: 99%
“…Endothelial dysfunction is characterized by reduced bioavailability of NO, an important vasodilator molecule produced by endothelial cells [ 35 ]. Typically, reduction in NO bioavailability is associated with increased production of reactive oxygen species and abnormal inflammatory response [ 3 , 27 , 32 , 57 ]. In such circumstances, vascular endothelium is dysfunctional, which can lead to the development of CVD and death [ 3 , 20 , 22 ].…”
Section: Vascular Effectmentioning
confidence: 99%